Privatization and the unusual case of Belarusian accession to the WTO - Edward J. Balistreri; Zoryana Olekseyuk; David G. Tarr (Bank of Finland, Institute for Economies in Transition (BOFIT), 2017)
The accession negotiations of Belarus to the WTO are unusual since, due to its obligations in the Eurasian Economic Union, WTO accession is not expected to impact its tariffs or formerly substantial trade distorting agricultural subsidies. Nonetheless, we estimate that WTO accession will increase welfare by 8.8 percent per year in Belarus in the medium term. We show that inclusion of (i) foreign direct investment; (ii) reduction on non-discriminatory barriers against services providers; and (iii) our model with imperfect competition and endogenous productivity effects together produce esti-mated gains eleven times larger than a model of perfect competition with only cross-border trade in services. Our analysis is enabled by our production of a dataset on both discriminatory and non-discriminatory barriers in services and their ad valorem equivalents. Based on a new dataset on labor productivity by sector and type of ownership, in our central model we estimate that privatization will increase welfare by 35.4 percent. We find substantial variance in the estimated gains from privatiza-tion depending on model assumptions; but all the estimates of the impacts of privatization indicate substantial welfare gains.
URN:NBN:fi:bof-201702271167
Keywords: D02; D58; F13; F14; L16; C68; 330